Christ as example: An analysis of the Christological Hymn of Philippians - Espírito Santo, Magno Lessa do (Vox Scripturae - Revista Teológica Internacional, 2015)
This article analyses how Paul makes use of hymnic material in his letters. After that, it realizes the exegesis of pericope from Philippians 2.6-11, pointing out its main linguistic – semantic aspects. Besides this, it presents how the community used the hymn, mainly, on the liturgy of baptism and studies the background of the hymn. Equally investigated, how the hymn confronts directly the fundamentals of the Roman imperial theology.